Specialities of Iranian traditions. (Journal of Oriental Studies, 2016)
This article was written about Iranian cultural wedding traditions. Iranians as the other countries,follow the main cultural wedding traditions, which have a beginning from the earliest times.
Keywords: Iran; culture; tradition; speciality